Urban Magic in Early Modern Spain - Tausiet, M. author. aut Link
XIV, 254 p.
Keywords: Drawing on the graphic and revealing evidence recorded by the different courts in early modern Saragossa, this book captures the spirit of an age when religious faith vied for people's hearts and minds with centuries-old beliefs in witchcraft and superstition.